An examination of Professor Shaikh's proposal to tame Harrodian instability - Reiner Franke (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
This note reconsiders a recent proposal by A. Shaikh to tame Harrodian instability (Metroeconomica 2009), where besides the utilization gap investment depends on the expected growth of demand. His stability result has, however, been criticized as not credible. The crucial point is that Shaikh's continuous-time treatment does not distinguish between forward and backward derivatives. In order to check whether or not this poses a problem, several slight modifications of the model in continuous and discrete time are formulated and investigated for their stability. Roughly speaking, it is found that unless one assumes (myopic) perfect foresight, the destabilizing Harrodian mechanism continues to be effective.
Keywords: C02; D84; E12; E30; 330; Hicks–Harrod adjustment principle; continuous-time versus discrete-time modelling; backward-looking versus forward-looking expectations